Identifikasi Model Generalized Space-time Autoregressive (GSTAR) untuk Nilai Inflasi di Pulau Sulawesi - Nur'Eni; Lusiyanti, D; Gunawan, I (Program Studi Matematika, Universitas Tadulako, 2021)
This study aims to identify a forecast model for the value of inflation at seven locations on the island of Sulawesi, namely Palu, Makassar, Gorontalo, Kendari, Manado, Mamuju and Palopo. Estimation of the parameters of the GSTAR model is carried out using the Ordinary Least Square (OLS) method with uniform location weights. The analysis results show that the GSTAR model (1,1) can be used to predict the value of inflation in Sulawesi Island.